Philip Roth. - Brauner, David (Manchester : Manchester University Press, 2007)
This is a groundbreaking study of the most important contemporary American novelist, Philip Roth. Reading the author alongside a number of his contemporaries, and focusing particularly on his later fiction, this book offers a highly accessible, informative and persuasive view of Roth as an intellectually adventurous and stylistically brilliant writer who constantly reinvents himself in surprising ways. At the heart of this book are a number of detailed and nuanced readings of Roth?s works both in terms of their relationships with each other and with fiction by Nathaniel Hawthorne, Thomas Pynch.
6 Fantasies of flight and flights of fancy: rewriting history and retreating from trauma in The Plot Against AmericaAfterword; Works cited; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; U; V; W; Y; Z.
Print version record.
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: Roth, Philip -- Criticism and interpretation; Roth, Philip; American fiction -- 20th century -- History and criticism; Roman américain -- 20e siècle -- Histoire et critique; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- General; American fiction; English; Languages & Literatures; American Literature; 1900-1999; Criticism, interpretation, etc